Antibacterial Activity of the Original Dietary Supplement Oxidal® in Vitro - Popova, Prof. Teodora P. (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Studies have been conducted to determine the antibacterial effect of Oxidal® and anolyte against Staphylococcus aureus and Escherichia coli. The bacterial strains tested showed high sensitivity to the dietary supplement Oxidal® and to anolyte, as well as to the control antibiotic Thiamphenicol. The mean MPC50 values of Oxidal® for Gram-positive bacteria S. aureus (0.21 ± 0.13 mg/ml) were lower than those for Gram-negative E. coli (0.55 ± 0.24 mg/ml). The dose that fully suppressed S. aureus growth was 0.86 ± 0.52 mg/ml, while for E. coli this dose was significantly higher - 2.40 ± 0.80 mg/ml (P<0.05). For the antibiotic Thiamphenicol, the results were opposite - the mean MPC50 values for E. coli (2.40 ± 0.80) were lower than those for S. aureus (3.71 ± 2.86). Under the influence of 10% Oxidal® solution, the amount of viable S. aureus and E. coli decreased by more than 30% over the untreated control after 20 min. After 45 minutes, only 37% of S. aureus cells and 19% of E. coli cells developed upon cultivation, and after 90 minutes of exposure, about 20% of the cells of the microorganisms understudy of both species remained viable. The fresh anolyte and the one stored for 1 year inactivated S. aureus and E. coli for 2 min in a suspension at a density of 106 cells/ml.